Risk of Arterial Thrombosis in Relation to Oral Contraceptives (RATIO) Study: Oral Contraceptives and the Risk of Ischemic Stroke - Kemmeren, Jeanet M.; Tanis, Bea C.; van den Bosch, Maurice A.A.J.; Bollen, Edward L.E.M.; Helmerhorst, Frans M.; van der Graaf, Yolanda; Rosendaal, Frits R.; Algra, Ale (Stroke (1970), 2002)
Background and Purpose — Epidemiological studies have shown an increased risk of venous thrombosis in women taking third-generation oral contraceptives, ie, those containing the progestogens desogestrel or gestodene. This study assesses the risk of ischemic stroke with several types of oral contraceptives. Methods — A multicenter, population-based, case-control study was performed in 9 Dutch centers in women aged 18 to 49 years. Women with a first ischemic stroke were compared with control women without vascular diseases. The control subjects were recruited by random-digit dialing and were stratified by age, area of residence, and year of stroke. All patients and control subjects filled in a questionnaire about the use of oral contraceptives and risk factors for ischemic stroke. Odds ratios were adjusted for the stratification factors. Results — Two hundred three women with an ischemic stroke and 925 control women were included. The risk of stroke in women using any type of oral contraceptives versus none was 2.3 (95% CI 1.6 to 3.3). Current users of first-generation oral contraceptives had an odds ratio of 1.7 (95% CI 0.7 to 4.4). Low-dose second-generation oral contraceptives increased the risk of stroke 2.4 times (95% CI 1.6 to 3.7), and third-generation oral contraceptives increased the risk of stroke 2.0 times (95% CI 1.2 to 3.5). The risk of stroke in women using third-generation oral contraceptives was not different from that in women using second-generation oral contraceptives (odds ratio 1.0, 95% CI 0.6 to 1.8). Conclusions — Third-generation oral contraceptives (containing desogestrel or gestodene) confer the same risk of first ischemic stroke as second-generation oral contraceptives (containing levonorgestrel).